Digitizing Odonata Specimens and Enhancing Data Accessibility through the BIDARA Database - Roslin, Ely Ezleen; Sapaat, Arney (Enhanced Knowledge in Sciences and Technology, 2024)
Natural history museum collections are an invaluable source of information on storing the remains biodiversity of the Earth from the past until present, particularly for providing detailed historical data and morphological reference specimens. The data and information are mostly store in physical form, and digitization of collections offers public access to the information of specimens and images data to discuss species ecological distribution and morphological for future actions on conservation efforts. many museum collections of Odonata around the world still lack comprehensive digitization, posing several challenges and limitations to researchers and educators. This study aims to set up baseline data of Odonata species in UTHM Natural History collection and to digitize Odonata specimens into Biodiversity Data Integration for Research Assets (BIDARA) database. This study also provides low-cost methods for digitization process, and images and information of digitized odonata specimens from UTHM Natural History collection into BIDARA, a biodiversity database platform develops under efforts of Centre of Research for Sustainable Uses of Natural Resources (COR-SUNR). This research conducts several steps for digitization process, from pre-digitization, during digitization and exporting images to BIDARA database. This study also discusses future recommendations for effective ways to manage biodiversity data.